The relationship between quantum management and organizational agility in Ministry of Roads and Urban Development of Golestan province, Iran - Alireza Sazesh; Seyed Ali Siadat (Dutch Journal of Finance and Management, 2018)
This study examined the relationship between quantum management and organizational agility in Ministry of Roads and Urban Development of Golestan province, Iran. It was a correlation-descriptive study and the statistical population was all employees of the Ministry of Roads and Urban Development Office of Golestan province, Iran in 2014. 166 individuals were selected as the sample and finally 154 questionnaires were analyzed. Data was analyzed using correlation and regression analysis. The results indicated that there was a significant positive relationship between the quantum management and organizational agility except quantum sense in the Ministry of Roads and Urban Development of Golestan province, Iran. Based on regression analysis, the organizational agility was affected by quantum management and if the managers of the Ministry of Roads and Urban Development of Golestan province, Iran use the quantum managing, it can be predicted that the organizational agility will be increased.
Keywords: 650; organizational agility; improved performance; strategy